Assessing Risk Management Capability of Public Sector Organizations Related to PPP Scheme Development for Water Supply in Indonesia - Pangeran M.H.; Pribadi K.S.; Wirahadikusumah R.D.; Notodarmojo S. (Civil Engineering Dimension, 2012)
The success of Public Private Partnership (PPP) for water supply investment is inseparable from the capability of risk management of the parties within the project. This study investigates the risk management capability of Indonesian local public sector organizations that are potentially involved in PPP schemes for water supply. A risk management maturity model based assessment tool probing the culture, process, experience, application and partnership aspects is used in the survey. The model describes risk management capability in four levels (ad-hoc, initial, competent, excellent). The survey shows that their risk management capability is still in-average at the initial stage (level 2), meaning that the adopted risk management postures are mostly supported only by unstructured, ad-hoc and non-formal processes. The result of this study can help decision makers in choosing appropriate risk management methods and tools to be used by the local public authorities for managing risks in PPP schemes.